Determinants influencing fraud prevention: Empirical evidence of listed non-financial joint stock firms - Nguyen, Thi Que; Trinh, Viet Giang; Tran, Binh Minh; Nguyen, Thi Xuan Hong; Truong, Thanh Hang (Edelweiss Applied Science and Technology, 2026)
This study identifies and measures the key governance factors influencing fraud prevention effectiveness within non-financial listed joint-stock firms in Vietnam, emphasizing the role of corporate governance in safeguarding organizational reputation and sustainability. Using a quantitative approach, data were gathered via a structured questionnaire from 467 valid respondents. Regression analyses were performed using SPSS 22 and SmartPLS 3.0 to assess the determinants of fraud prevention effectiveness. The results indicate that all five components of the internal control system, control environment, risk assessment, control activities, information and communication, and monitoring, significantly impact fraud prevention. Additionally, audit quality (AQ) and internal auditing (IA) demonstrate positive and statistically significant effects on mitigating fraud risks. The research underscores that robust internal controls, high audit quality, and active internal auditing are critical pillars for effective fraud risk management in the Vietnamese corporate context. Firms are advised to strengthen their internal control frameworks and prioritize investments in internal audit processes. Furthermore, enhancing professional training and audit quality is essential for improving fraud prevention effectiveness and long-term firm performance.